Papain-like Protease Peptides as Construction Material for the SARS-CoV-2 Vaccine Design Candidate: In-silico Study - Mardianingrum, Richa; Pertiwi, Nur Ihsani; Rizkuloh, Lina Rahmawati; Ikram, Nur Kusaira Khairul; Ruswanto, Ruswanto (Jurnal Kimia Valensi, 2025)
COVID-19 remains a major global health threat. In addition to implementing health protocols and consuming supplements, proactive prevention strategies are essential to limit the spread of the virus. One of the most promising approaches is the use of vaccines, particularly peptide-based vaccines, which are under active development. This study aimed to design a peptide vaccine derived from the SARS-CoV-2 papain-like protease (PLpro) and evaluate its interaction with key components of the human immune system, namely Toll-like receptor 3 (TLR3), major histocompatibility complex class I (MHC-I), and class II (MHC-II). The research employed an immunoinformatics approach utilizing NetCTL, IEDB Tepitool, PEP-FOLD3, trRosetta, HDOCK, GalaxyRefine2, and other molecular modeling tools. The designed vaccine construct was visualized in 3D using trRosetta and validated through ERRAT2, achieving a 100% quality score, indicating excellent structural integrity. The docking simulations demonstrated stable interactions between the vaccine and the immune receptors, suggesting strong immunogenic potential. In conclusion, the in silico-designed peptide vaccine based on SARS-CoV-2 PLpro shows promise in triggering immune responses through stable binding with TLR3, MHC-I, and MHC-II, highlighting its potential as a candidate for further experimental validation in COVID-19 vaccine development.